2012
DOI: 10.1039/c2nr30432e
|View full text |Cite
|
Sign up to set email alerts
|

Anion-controlled morphologies and spectral features of cyanine-based nanoGUMBOS – an improved photosensitizer

Abstract: The ability to control the morphologies and spectral properties of organic low-dimensional nanomaterials is of paramount importance. The research reported herein demonstrates a template-free approach to tailored morphological and optical properties for a novel class of pseudoisocyanine (PIC)-based fluorescent organic nanoparticles derived from a group of uniform materials based on organic salts (GUMBOS). The synthesized nanoscale PIC-based particles (termed nanoGUMBOS), [PIC][NTf(2)] and [PIC][BETI], exhibit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
60
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 54 publications
0
60
1
2
Order By: Relevance
“…At the same time new features like enhanced thermal stability and solubility were introduced 24. Salt metathesis using two‐phase liquid/liquid systems is the most commonly used technique 25, 26, 27. However, it often requires several purification steps either by recrystallization or column chromatography, which lowers the yield of the desired organic salt.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time new features like enhanced thermal stability and solubility were introduced 24. Salt metathesis using two‐phase liquid/liquid systems is the most commonly used technique 25, 26, 27. However, it often requires several purification steps either by recrystallization or column chromatography, which lowers the yield of the desired organic salt.…”
Section: Introductionmentioning
confidence: 99%
“…1 The aggregation patterns of the dye molecules exhibit red shift (J-type) and blue shift (H-type) in absorption bands. 2,3 TTBC is a twodimensional planar molecule that can form secondary interactions, yielding intriguing supramolecular structure. This cyanine dye undergoes both H-and J-type aggregation by shortrange noncovalent interactions, such as dipole−dipole interactions, π−π stacking, and hydrogen bonding.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nevertheless, the size-control of melt-emulsionquench-derived nanoparticles was still considered a major challenge. In some of our more recent studies, a reprecipitation approach commonly employed in the synthesis of organic nanoparticles [22,23] was extended to the preparation of nanoGUMBOS in an aqueous medium [12,14,18,19]. Although this method can be used to produce nanoparticles with average sizes in the nanometer regime, it is difficult to deliver nanoparticles smaller than 20 nm without using additives such as surfactants or polymers [24].…”
mentioning
confidence: 99%
“…NanoGUMBOS thus combine the versatility of GUMBOS with the enhanced properties often obtained at the nanoscale, offering the flexible design of organic nanomaterials. Within the last few years, nanoGUMBOS which possess fluorescent [12][13][14], magnetic [15], luminescent [16], pHsensitive [17], optoelectronic [18], and anticancer [19] properties have been described. Previous studies from our laboratory have demonstrated the wide tunability in the spectral and physical properties, as well as the morphologies of nanoGUMBOS through variation in the associated counter ion [14,18,20].…”
mentioning
confidence: 99%